Analisis Strategi Marketing Funding di Bank BRISyariah KC Purwokerto - Mila Fursiana Salma Musfiroh; Muhammad Rifai; Nada Diana (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2019)
High level of competition in banks in fighting over third party funds, spur banks to continue to try to lure their customers in various ways. No matter how good the company's management, segmentation, target market, will not run if it is not followed by the right strategy. Strategy is the steps that must be carried out by a company to achieve goals. While marketing is a process of creating, offering, andex changing valuable products to other parties to achieve the goals of a company. So the marketing strategy is the steps taken to take over the decision carefully toget the goals and objectives to be achieved by taking into account the conditions ofthe surrounding environment. This is done to get the wants and needs to beachieved. The same goes for BRISyariah KC Purwokerto. The purpose of this study is to determine the funding marketing strategy in raising funds, and how the impactof the marketing strategy implemented by the funding department. In this study using qualitative methods, the analysis process uses data reduction, data display,data verification and drawing conclusions. BRISyariah KC Purwokerto's strategy in marketing in terms of funding to attract public attention using advertising, personal selling, publicity and sales promotion strategies. Of course, this is able to spur the growth of bank financial assets, seen from the acquisition of individual funding team targets in August reached 98.5%, increasing to 102.4% in September from the target of 1 billion per employee. the division and supervision targets perSeptember reached 96% of the 260 billion target.